2020
DOI: 10.1039/d0nj02149k
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of new zinc(ii) complexes with N2O2 chelating thiosemicarbazidato ligands; investigation of the relationship between their DNA interaction and in vitro antiproliferative activity towards human cancer cells

Abstract: New candidates to become DNA-targeting antiproliferative agents: Zinc(ii) complexes bearing N2O2-thiosemicarbazidato ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated that presence of a methoxy group (–OCH 3 ) in some molecules can significantly increase biological activity, particularly antiproliferative performance. 42,46,72,73 Unsubstituted Ni II -L 1 (with R = H) did not present antiproliferative activity in any of the tested cell lines (IC 50 > 100 μM). In contrast, its methoxy-containing derivative Ni II -L 2 (with R = –OCH 3 ) was the most potent anticancer agent (IC 50 = 3.4–11.3 μM).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have demonstrated that presence of a methoxy group (–OCH 3 ) in some molecules can significantly increase biological activity, particularly antiproliferative performance. 42,46,72,73 Unsubstituted Ni II -L 1 (with R = H) did not present antiproliferative activity in any of the tested cell lines (IC 50 > 100 μM). In contrast, its methoxy-containing derivative Ni II -L 2 (with R = –OCH 3 ) was the most potent anticancer agent (IC 50 = 3.4–11.3 μM).…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, it was not possible to establish a clear correlation when including the methoxy group, in agreement with previous reports. 42,46,72,73 More salophen derivatives are required to assess the role played by substituents (R = H or -OCH 3 ) in the aromatic rings and further studies to examine the pathways of action through which these kinds of complexes act.…”
Section: Cell Viability Studymentioning
confidence: 99%
“…31 In the last few years different classes of zinc coordination complexes have shown good potential in diverse applications, in nonlinear optics, in photo-catalysis and in several diseases, and as anti-inflammatory, anti-diabetic, antimicrobial, antioxidant, and antitumor agents. [32][33][34][35][36][37][38][39][40] As a part of our efforts to explore the non-covalent interactions in coordination compounds, herein, we have designed and prepared two Zn(II) complexes (1 and 2) using a newly synthesized [(1-methylimidazol-2-yl)methylene] isonicotinohydrazide [HL] ligand in aqueous medium. Single crystal X-ray analysis shows that complex 1 is a distorted octahedron whereas complex 2 is a distorted tetrahedron in nature.…”
Section: Introductionmentioning
confidence: 99%
“…31 In the last few years different classes of zinc coordination complexes have shown good potential in diverse applications, in nonlinear optics, in photo-catalysis and in several diseases, and as anti-inflammatory, anti-diabetic, antimicrobial, antioxidant, and antitumor agents. 32–40…”
Section: Introductionmentioning
confidence: 99%